Corporate Board Size and Its Impact on Firm Performance: An Empirical Study on Commercial Banks - Dongol, Padam (Journal of Kathmandu BernHardt College, 2022)
This study examines the corporate board size and its impact on the firm performance. This study identifies the banks with directors less than seven on the board and directors equal to or more than seven, based on eight years of data taken from 2013 to 2020 of Nepalese commercial banks. The study covers 27 banks as sample banks for the study. The Return on equity and Return on assets measures the firm performance. Corporate board size and firm performance are measured by using the Independent Sample t-test. The finding of results demonstrates that banks with less than seven directors on the board and banks with equal to or more than seven directors on the board have yet to find a significant impact on the firm performance of the commercial banks.